Crucial Players for Inter-Organelle Communication: PI5P4Ks and Their Lipid Product PI-4,5-P2 Come to the Surface - Ravi, Archna; Palamiuc, Lavinia; Emerling, Brooke M. (Frontiers in Cell and Developmental Biology, 2022)
While organelles are individual compartments with specialized functions, it is becoming clear that organellar communication is essential for maintaining cellular homeostasis. This cooperation is carried out by various interactions taking place on the membranes of organelles. The membranes themselves contain a multitude of proteins and lipids that mediate these connections and one such class of molecules facilitating these relations are the phospholipids. There are several phospholipids, but the focus of this perspective is on a minor group called the phosphoinositides (PIs) and specifically, phosphatidylinositol 4,5-bisphosphate (PI-4,5-P2). This PI, on intracellular membranes, is largely generated by the non-canonical Type II PIPKs, namely, Phosphotidylinositol-5-phosphate-4-kinases (PI5P4Ks). These evolutionarily conserved enzymes are emerging as key stress response players in cells. Further, PI5P4Ks have been shown to modulate pathways by regulating organelle crosstalk, revealing roles in preserving metabolic homeostasis. Here we will attempt to summarize the functions of the PI5P4Ks and their product PI-4,5-P2 in facilitating inter-organelle communication and how they impact cellular health as well as their relevance to human diseases.